Obtenção e caracterização de nanosistemas magnéticos derivados do lcc - Ribeiro, Viviane Gomes Pereira (2013)
Nanotechnology has received great prominence in recent years due to the versatility of new materials and its applications at the various sectors of society. The functionalized magnetic nanoparticles have been the focus of intense research because of the ability to use on different systems, with emphasis on the catalytic processes of environmental decontamination. In particular, we have seen a growing demand for hybrid catalysts capable of utilizing sunlight, constructed from TiO2 particles by photosensitised dyes. Thus, this study aimed to develop a new magnetic nanosystem, based on use of meso-porphyrins derived from Cashew Nut Shell Liquid (CNSL), coated with TiO2, with potential application in heterogeneous photocatalysis. Moreover, produce a new ferrofluid derived biomass from the anacardic acid (AA MAG). To this end, were synthesized Fe3O4 nanoparticles with an average size of 11nm, coated with a 1st layer of oleic acid and a 2nd layer of meso-porphyrin (3-n-PDPP). This nanosystem also was covered with a layer of TiO2. This procedure produced a new magnetic nanosystem of porphyrin (NMP). The new ferrofluid AA-MAG and magnetic nanosystems were characterized by Transmission Electron Microscopy (TEM), infrared spectroscopy, Thermal analysis (TG) and magnetization curves. The results showed that NMP showed good thermal stability, superparamagnetic behavior and dimension nanometric (≈ 14nm). The fluorescent properties were little affected, which enables its application in photocatalytic systems.